The Biology, Ecology and Medicine Faculty of Dnipropetrovsk National University after Oles’ Gonchar - Pakhomov, Olexandr (Acta Agraria Debreceniensis, 2010)
The historical rewiev of Biology, Ecology and Medicine Faculty is presented. The Faculty of Biology, Ecology and Medicine has 7 Departments, Aquarium complex, Zoological Museum, Vivarium and Herbarium. It works in cooperation with the Research Institute of Biology, Botanical Garden, O. L. Bel’gard International Biosphere Station, and Biological Station of DNU and forms the regional Centre of Science, Education and Culture in the field of Biology, Ecology and Nature Conservation in Central Ukraine. The Faculty proposes courses in the following specialities: Biology, Zoology, Botany, Microbiology and Virology, Biochemistry, Physiology, Ecology, Environmental Protection and Balanced Nature Management. All of them have the highest IV level of accreditation. Students get a pedagogical education.